2002
DOI: 10.1159/000069790
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Serum Assays in Breast Cancer: Tumor Specificities and Reference Levels

Abstract: The aim of the study was to establish reference ranges and to explore the tumor specificities of two automated assays for MUC1. Sera from 124 female blood donors, 144 patients with benign disease of the breast, 69 patients with stage I, 75 with stage II, 89 with stage III and 38 patients with stage IV breast cancer were analyzed for MUC1 levels using two automated immunometric assays employing assay antibody pairs Ma695/Ma552 and BC2/GP1.4, respectively. All subjects were female. The Ma695/Ma552 assay yielded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In stage III and IV tumors, the Ma695/Ma552 assay showed higher sensitivity than the BC2/GP1.4 assay. 236 In addition, this study demonstrated that reference limits for MUC1 established with sera from female blood donors will lead to large numbers of false positive results in patients with benign breast disease. Finally, standardization of MUC1 assays seems to be theoretically impossible due to the structural differences between normal and tumor-associated MUC1.…”
Section: Tumor Serum Assays Based On Mucin Antigens and Mucin-reamentioning
confidence: 84%
“…In stage III and IV tumors, the Ma695/Ma552 assay showed higher sensitivity than the BC2/GP1.4 assay. 236 In addition, this study demonstrated that reference limits for MUC1 established with sera from female blood donors will lead to large numbers of false positive results in patients with benign breast disease. Finally, standardization of MUC1 assays seems to be theoretically impossible due to the structural differences between normal and tumor-associated MUC1.…”
Section: Tumor Serum Assays Based On Mucin Antigens and Mucin-reamentioning
confidence: 84%
“…For example, poor prognosis of breast cancer correlates with increased quantities of mucins, a large protein family with extensive glycosylation. One of these proteins, mucin 1 (MUC1) is an approved Food and Drug Administration (FDA) biomarker for breast cancer through the use of a serum immunoassay test [13]. While MUC1 is a commonly used diagnostic indicator for detecting breast cancer, its overexpression does not necessarily correlate with distance metastasis [14].…”
Section: Introductionmentioning
confidence: 99%
“…in a recent systematic study of females with either no disease, benign disease, stage i, stage ii, stage iii, or stage iV breast cancer, MUC-1 serum levels reflected a distinction between different groups. MUc1 levels were slightly elevated in women with benign disease compared to healthy controls, and very significantly elevated with more advanced stages of the disease (11). the value of MUc-1 for tumor staging is especially high because MUc-1 is expressed very early in the transformation process.…”
Section: Imaging Target-umuc-1 Tumor Antigenmentioning
confidence: 90%